Mebendazole vs. mebendazole-pyrantel pamoate for soil-transmitted helminthiasis infection in children - Fereza Amelia; Muhammad Ali; Syahril Pasaribu (Indonesian Pediatric Society Publishing House, 2013)
Abstract Background Soil-transmitted helminthiasis (STH) is the most common infection in developing countries. Although it causes high morbidity, it is still difficult to find the efficacy dose of antihelmintics for its treatment. Objective To determine the efficacy ofmebendazole and mebendazole- pyrantel pamoate in treating STH infection in children. Methods We conducted a randomized open-label controlled trial from July to September 2009 in Secanggang, Langkat District, North Sumatera Province, Indonesia, on primary school-aged children. Before the intervention, data on age, sex, nutritional status, and STH infection status were collected. The children were randomized into two groups. Children in group I received a single dose of 500 mgmebendazole while they in group II received a single dose of 500 mg of mebendazole combined with 10 mg/ kgBW of pyrantel pamoate. We examined subjects' stool specimens on days 7, 14, 21, and 28 after treatment to determine cure rates and egg reductions. Statistical analyses were performed by Chi square and student's Ttest with 95% confidence intervals and P values of< 0.05 considered to be significant. Results We found that the cure rates were 95.4%, 78.5%, and893% for Ascaris lumbricoides, Trichuris trichiura, and mixed (A lumbricoides and T trichiura) infections, respectively, in the mebendazole group. The cure rates were 98.5%, 89.2%, and 90.2% for A lumbricoides, T trichiura, and mixed infections, respectively, in the mebendazolepyrantel pamoate group. Although the cure rate results were not significantly different between the 2 treatment groups, the total eggs per gram (EPG) was significantly lower for both A lumbricoides and T trichiura infections (P=0.001 and P=0.002, respectively) in the combination therapy group than in the mebendazole alone group. Conclusion Mebendazole in combination with pyrantel pamoate has higher efficacy than mebendazole alone in terms of faster egg reduction rates. However, the cure rates of these two antihelmintics regimens are similar.